Stomatal Density, Stomatal Index, Stomatal Size and Transpiration Rates in Agave americana and Aloe vera - Adeniran, Sunday; Abdulrahaman, Abdullahi; Sagaya, Abdulquadri (FUDMA Journal of Sciences, 2026)
The need to reduce water wastage on irrigation of plants in view of the global water crisis necessitates the delimitation of some leaf epidermal features which are relevant to water use efficiency (WUE). Two ornamental plant species namely: Agave americana Linn. and Aloe vera Tourn. & Linn. were studied to determine anatomical and morphological features which are adaptations to water stress and can serve as indices for frequency of watering. The species were propagated in a greenhouse and subjected to 4 watering frequencies each with 5 varying soil moisture contents. After six weeks of watering in the greenhouse, anatomical studies using a light microscope were also carried out. Anatomical adaptations include low stomatal density, low stomatal index and small stomata and low transpiration rate. Leaves with high stomatal density, stomatal index and large stomata also encouraged high rate of transpiration.  Analysis of Variance and Duncan’s Multiple Range Test showed that there were significant differences p
Keywords: Agave americana; Aloe vera; Stomata; Transpiration rate; water use efficiency (WUE)